Enriching the PhD Experience. - The, Sun (The Sun, 2018)
A Doctor of Philosophy or PhD is the higest level of education degree you can earn from Asia e University (AeU) from any part of the world. You can study by fully online mode from anywhere, anytime. While receiving a PhD can be a long and difficult road, it may be worth it in terms of enriched knowledge, job prospects and professional opportunities.